Comparative Study of Routing Techniques in Wireless Sensor Network - Dhaigude Tanaji Anandrao, Mr; Latha Parthiban, Dr; R. A. Veer, Mr; L C Siddanna Gowd, Dr; Avinash J. Kokare, Prof. (International Journal of Engineering and Technology, 2018)
A Wireless Sensor Network is made up of small sensor nodes. These nodes are deployed in monitoring area. All nodes collect necessary data and route this data to centre server. A WSN should have self-organizing capability, as nodes positions are not determined in advance. Important factor in WSN is co-operation between nodes. Depending on WSN architecture and application, routing between nodes can vary. This paper presents a comparative study of different routing protocols/algorithm in WSN. Depending on network organization, WSN routing algorithms gets divided into 3 types, i.e. location based, hierarchical and flat. These routing algorithms can be divided further into sub types, depending on how an algorithm/protocol operates. This paper presents advantages and limitations of each routing algorithm.Â